Seismic vulnerability of existing buildings: non-invasive approach for dynamic behaviour assessment - Acunzo, Gianluca; Vicentino, Michele; Bottaro, Antonio (GEOmedia, 2018)
This paper presents a brief overview of the concept of seismic risk, with particular regard to existing civil buildings. Given that the seismic risk can be expressed as a combination involving seismic hazard and seismic vulnerability, these aspects are both discussed, describing the factors that lead to the expected seismic input at the base of a building as well as the ones determining its vulnerability. The way a building tends to react when it is subject to an external vibration is closely connected to its geometrical and mechanical features, which determine what in structural engineering are commonly called "vibrational modes”. As a consequence, an accurate estimation of these modes is a fundamental condition in order to assess the structural response under seismic action. Several experimental techniques aimed at the identification of the vibrational modes for existing buildings and the way in which such parameters can be used in the vulnerability assessment field are described in the present work.